The detection of Jonah gene transcripts in Drosophila by in situ hybridization. - Akam, M E (1985)
The Jonah genes constitute a family of approximately 20 genes expressed at two periods during the development of Drosophila melanogaster. They are expressed only in the midgut, where they yield very abundant transcripts of approximately 900 bases. The function of their products is not known. We have used in situ hybridization to show that transcripts homologous to two members of the Jonah family have quite different distributions within the midgut. Transcripts closely homologous to Jon65Aiv are expressed throughout most of the anterior midgut and in the posterior section of the middle midgut. Transcripts closely homologous to Jon99C beta are expressed only in the anterior region of the posterior midgut.